PENGARUH APLIKASI URIN KAMBING DAN PUPUK CAIR ORGANIK KOMERSIAL TERHADAP BEBERAPA PARAMETER AGRONOMI PADA TANAMAN PAKAN INDIGOFERA SP. - L. Abdullah; D.D.S. Budhie; A.D. Lubis (Udayana University)
An experiment has been done during 6 months period in order to study the effect of goat urine and comersial liquid organic fertilizer (NASA®) as fertizers on some agronomic parameters which are related with potential forage production. Completely randomized design was used in this experiment which is consist of PO = control, P1 = 50% goat urine + 50% mineral water, P2= 100% urine, P3= NASA 0.25%, P4 NASA= NASA 0.50% and P5 = NASA 0.75%, with 5 repetitions. Some agronomic parameters observed were biomass production of tajuk, leaves dry matter production, numbers of leafs and leaf square. To observe the effect of goat urine observation were conducted in two growth periodes. The results of the experiment showed that the application of goat urine and comercial liquid organic fertilizer produce better results in all treatments compared to control. 100% goat urine treatment showed that better results in all parameters compared to commercial liquid organic fertilizers